Defects and Safety of NiTi Root Canal Instruments: A Systematic Review and Meta-Analysis - Yon, Madeline Jun-yu; Tang, Mark Ho-yeung; Cheung, Gary Shun-pan (Frontiers in Dental Medicine, 2021)
Aim: To review the reported defect and fracture rates of various NiTi instrumentation systems and identify factors that may influence the chance of NiTi file separation clinically. Data sources: PubMed, EMBASE and SCOPUS with controlled vocabulary and keywords in various combinations to identify articles that reported on the defects and/or fracture of NiTi instrument used clinically (Jan 1980 till Mar 2020), with additional search manually by going through the list of references of the initially screened articles. Those satisfying the inclusion and exclusion criteria were entered into the analysis. Study eligibility criteria, participants and interventions: All studies from the said databases reporting on NiTi root canal instruments that were deformed or separated during normal clinical use. Study appraisal and synthesis methods: Studies with data available and suitable for meta-analysis were grouped according to the general design of the NiTi instruments for comparison. Safety quotient value was calculated based on the rate of instrument distortion and fracture. Results: Various instrument designs exhibited different incidences of distortion and fracture, hence a different “safety quotient” (ratio of the amount of deformed instruments to that of fractures in use). Heat-treated files showed the highest safety quotient value. All brands of NiTi file demonstrated a statistically significantly lower incidence of fracture, if treated as disposable instruments after clinical use in a patient. Limitations: Inclusion of articles written in English only, and grouping of file systems into general design types in the analysis. Conclusions and implications of key findings: NiTi endodontic files should be scrutinised for defects before being used in the root canal. Disposing the NiTi instruments after clinical use in a patient (so-called “single use”) is recommended for minimising fracture clinically. Certain instrument designs tend to show discernible deformation before they should fracture in the next use.